BALB/c mice deficient in CD4 T cell IL-4Rα expression control Leishmania mexicana Load although female but not male mice develop a healer phenotype. - Karen J Bryson; Owain R Millington; Thabang Mokgethi; H Adrienne McGachy; Frank Brombacher; James Alexander (Public Library of Science (PLoS), 2011)
Immunologically intact BALB/c mice infected with Leishmania mexicana develop non-healing progressively growing lesions associated with a biased Th2 response while similarly infected IL-4Rα-deficient mice fail to develop lesions and develop a robust Th1 response. In order to determine the functional target(s) for IL-4/IL-13 inducing non-healing disease, the course of L. mexicana infection was monitored in mice lacking IL-4Rα expression in specific cellular compartments. A deficiency of IL-4Rα expression on macrophages/neutrophils (in LysM(cre)IL-4Rα(-/lox) animals) had minimal effect on the outcome of L. mexicana infection compared with control (IL-4Rα(-/flox)) mice. In contrast, CD4(+) T cell specific (Lck(cre)IL-4Rα(-/lox)) IL-4Rα(-/-) mice infected with L. mexicana developed small lesions, which subsequently healed in female mice, but persisted in adult male mice. While a strong Th1 response was manifest in both male and female CD4(+) T cell specific IL-4Rα(-/-) mice infected with L. mexicana, induction of IL-4 was manifest in males but not females, independently of CD4(+) T cell IL-4 responsiveness. Similar results were obtained using pan-T cell specific (iLck(cre)IL-4Rα(-/lox)) IL-4Rα(-/-) mice. Collectively these data demonstrate that upon infection with L. mexicana, initial lesion growth in BALB/c mice is dependent on non-T cell population(s) responsive to IL-4/IL-13 while progressive infection is dependent on CD4(+) T cells responsive to IL-4.